EFEKTIVITAS PENGGUNAAN BAJU KATETER TERHADAP TINGKAT KEMUDAHAN DAN KENYAMANAN BERAKTIVITAS PADA PASIEN DENGAN TERPASANG KATETER - Ridlo Muhammad Fahri, Ipnu; Suparti, Sri; Dwi Rahayu, Intan (Universitas Kadiri, 2024)
Outpatients with urinary disorders generally receive procedures like catheter insertion. Patients with a catheter often find it difficult to perform activities, including outpatient care. Therefore, there is a need for catheter clothing to facilitate and provide comfort for patients when active, even with a catheter in place. This study aims to determine the effectiveness of catheter clothing on the ease and comfort of activity in patients with a catheter. This research uses a quantitative method, with a Pre-Experimental with a cross-over design approach. The sample in this study was outpatients with a catheter who could perform activities/mobility independently or with assistance. There were 23 respondents, with the sample collection technique being random sampling. Data analysis used the Mann-Whitney Test. This study showed a significant difference indicating ease and comfort of activity between regular clothing and catheter clothing, with a value of z = -5.830, p = 0.001, and r = -1.21. This suggests a significant effect in the difference in ease and comfort between regular and catheter clothing. Conclusion : Using catheter clothing effectively increases ease and comfort in outpatients with urinary disorders who have a catheter in place. Keywords : Catheter Clothing, Outpatients, Catheterized Patients, Ease, Comfort